ORAL HEALTH PROMOTION AT SCHOOL: EXPERIENCE REPORT - Nunes Maia, Djanny (Health and Society, 2023)
The Health at School Program presents itself as a concrete form of health promotion of extreme relevance for school assistance, facilitating the contact of the population with dental services. Objective: To expose the carrying out of health program activities at the Elementary School Cleudomir Begot in the region of Ananindeua- Pará. Methods: The actions involved students aged 05 and 13 years. Site visits were carried out to collect all data from the educational institution and planning activities. Audiovisual educational material was used on the ideal brushing technique; activity addressing the theme “diet” and guidance on oral hygiene. Experience report: The two moments in which the activities were carried out were extremely fruitful and the students who were the target audience of the actions, which added to the cooperation of the primary care team, resulted in success in the objectives of health promotion and protection. specific. Conclusion: Carrying out educational actions in the school environment through the health at school program is very important to improve the quality of dental health in the student population.